Considering urban tourism in strategic spatial planning - David Klepej; Naja Marot (Annals of Tourism Research Empirical Insights)
This paper addresses how strategic spatial planning is considering urban tourism, a phenomenon that has an increasing impact on the development of cities. A research approach interlinking urban tourism and spatial planning is conceptualised based on responsiveness theory and applied to a case study of ten medium-sized Central European cities. Descriptive statistical analysis of the presence of tourism in cities and policy analysis of strategic spatial planning documents enable a comparison analysis of the level of consideration of tourism alongside screening of proposed tourism-related measures. The paper reveals that strategic spatial planning documents are not responsive enough to tourism growth, and there is a lack of strategic measures steering towards sustainable tourism development in cities.